Menopausal Symptoms in Underserved and Homeless Women Living in Extreme Temperatures in the Southwest - Mahnoor Mukarram; Veena Rao; Maheeyah Mukarram; David M. Hondula; Matthew R. Buras; Juliana M. Kling (Mary Ann Liebert, 2021)
Background: Little is known about menopausal symptoms in underserved women. Aim: To better understand self-reported menopausal symptoms in underserved and homeless women living in extreme heat during different seasons. Methods: A cross-sectional study, including the Greene Climacteric Scale (GCS), climate-related questions, and demographics was administered June to August of 2017 and December to February 2018 to women 40?65 years of age. Results: In 104 predominantly Hispanic (56%), uninsured (53%), menopausal (56%), and mid-aged (50???9.5) women, 57% reported any bother, while 20% of these women reported ?quite a bit? or ?extreme? bother from hot flushes. The total GCS score was n?=?104: Mean (SD) 19.8 (15.3); out of 63 indicating significant symptoms, the psychological and somatic clusters were highest. Women did not think temperature outside influenced their menopausal symptoms at either time point (69% in winter vs. 57% in summer, p?=?0.23). In multivariable analyses after adjusting for race, body mass index, and living situation neither season nor temperature was associated with self-reported hot flush bother. While one-third of women reported becoming ill from the heat, 90% of women reported not seeking care from a doctor for their illness. Conclusion: Menopausal, underserved, homeless women living in Arizona reported few vasomotor symptoms regardless of season, and endorsed psychological and somatic complaints. Socioeconomic factors may influence types of bothersome menopausal symptoms in this population of women.